2014
DOI: 10.1111/ijcs.12078
|View full text |Cite
|
Sign up to set email alerts
|

The effect of consumers' involvement and innovativeness on the utilization of fashion wardrobe

Abstract: This study proposed wardrobe utilization as a means of explaining consumer clothing use behaviour, and aimed to explore its relationship with other antecedent variables. We posit that use innovativeness functions as an antecedent of wardrobe utilization within a model comprised of fashion-related variables, such as fashion innovativeness and fashion involvement. An empirical study was conducted to test this relationship with 211 adult women between the ages of 20 and 40 years. In order to calculate wardrobe ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Goldsmith (2000) asserted that fashion innovativeness is a predictor of consumers' tendency to purchase new fashionable clothing. In a recent study by Choo et al (2014), consumers with high fashion innovativeness were found to be more likely to purchase new and trendy products/services. Accordingly, consumers with high fashion innovativeness are likely to perceive a new technology (e.g., 3D printing) positively and favorably and thus to develop the intention to try it.…”
Section: The Effects Of Fashion Innovativeness On Attitudes Towards 3mentioning
confidence: 95%
“…Goldsmith (2000) asserted that fashion innovativeness is a predictor of consumers' tendency to purchase new fashionable clothing. In a recent study by Choo et al (2014), consumers with high fashion innovativeness were found to be more likely to purchase new and trendy products/services. Accordingly, consumers with high fashion innovativeness are likely to perceive a new technology (e.g., 3D printing) positively and favorably and thus to develop the intention to try it.…”
Section: The Effects Of Fashion Innovativeness On Attitudes Towards 3mentioning
confidence: 95%
“…Specially, research shows that consumers' Internet usage has a positive effect on online buying and is significantly linked with socio-economic characteristics (Wu et al, 2011). Consumer creativity includes an openness to new ideas and seeking new experiences, which solves problems with personal knowledge (Choo et al, 2014). Online retailers should further identify existing gaps between their own desired level service performance and customer expectations.…”
Section: Innovation-based Capability and Value Offeringmentioning
confidence: 99%
“…Social values were measured by 13 items adapted from Wiedmann, Hennigs, and Siebels (2009) and Loureiro and de Araújo (2014). Involvement comprised seven items adapted from Choo et al (2014). The construct of consumer engagement was composed of 16 items as proposed by Kumar and Pansari (2016).…”
Section: Variable and Measurementmentioning
confidence: 99%